Fuzzy Process Accuracy Index to Evaluate Risk Assessment of Drought Effects in Turkey - Kahraman, Cengi̇z; Kaya, İhsan (Informa UK Limited, 2009)
ABSTRACT Risk assessment provides a systematic procedure for predicting potential risks to human health or the environment. In the literature, many techniques have been used for risk assessment. In this article, process capability indices are used for this aim. The fullness rates of the dams in Istanbul are analyzed for the harmful effects of the drought by the help of process capability indices. Additionally, the process accuracy index (C a ), which measures the degree of the process centering and gives alerts when the process mean departures from the target value, is used for risk assessment. Its distinctive feature is used to determine the mean of the fullness rates departures from the target value. The results are analyzed to improve precautions. The C a index is also analyzed when the critical parameters are defined as linguistic terms. The specification limits and mean are defined by triangular and trapezoidal fuzzy numbers, then the fuzzy set theory is applied to obtain fuzzy process capability ind...